2020
DOI: 10.31234/osf.io/t7yf9
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gender Essentialism and the Mental Representation of Transgender Women and Men: A Multimethod Investigation of Stereotype Content

Abstract: Social category systems – such as nationality, class, and gender – are constantly shifting. How are emergent social groups, which had previously not been societally recognized, mentally represented alongside more established groups? The growing visibility of transgender women and men in the US is an opportunity to observe this sort of cultural shift. Across three diverse methods of stereotype measurement, we assessed characteristics associated with transgender women and men and compared them to the stereotypes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 81 publications
0
3
0
Order By: Relevance
“…Across both sexual orientation and race, being part of a non-prototypical group had more influence on people's prescriptions than being a particular gender; people didn't desire gay, Black, Asian, Latino, and Middle-Eastern men and women to act as differently from one another as they desired straight and White men and women to act. Unpublished research on representations of transgender men and women have found a similar lack of gender differentiation within nonprototypical targets (Gallagher & Bodenhausen, 2021), a phenomenon they label as "degendering". Other work has also found that global stereotypes around competence and warmth for Black men and women show more similarity than the same stereotypes between White men and women (Coles & Pasek, 2020), further supporting the conclusion that gender differentiation is muted within non-prototypical groups.…”
Section: Discussionmentioning
confidence: 96%
“…Across both sexual orientation and race, being part of a non-prototypical group had more influence on people's prescriptions than being a particular gender; people didn't desire gay, Black, Asian, Latino, and Middle-Eastern men and women to act as differently from one another as they desired straight and White men and women to act. Unpublished research on representations of transgender men and women have found a similar lack of gender differentiation within nonprototypical targets (Gallagher & Bodenhausen, 2021), a phenomenon they label as "degendering". Other work has also found that global stereotypes around competence and warmth for Black men and women show more similarity than the same stereotypes between White men and women (Coles & Pasek, 2020), further supporting the conclusion that gender differentiation is muted within non-prototypical groups.…”
Section: Discussionmentioning
confidence: 96%
“…This implies that the normative pressures on minoritized groups fluctuate depending upon which aspect of their identity is foregrounded. Research on representations of transgender men and women has found a similar lack of gender differentiation within minoritized targets (Gallagher & Bodenhausen, 2021), a phenomenon they label as "de-gendering." Other work has also found that global stereotypes around competence and warmth for Black men and women show more similarity than the same stereotypes between White men and women (Coles & Pasek, 2020), further supporting the conclusion that gender differentiation is reduced within minoritized groups.…”
Section: Discussionmentioning
confidence: 98%
“…(2010), Yzerbyt, Corneille, and Estrada (2001), Pauker et al. (2016), and Gallagher and Bodenhausen (2021) for findings that support a positive relationship between essentialism and stereotyping. See Ritchie and Knobe (2020) and Bailey and Knobe (2021) for alternative views.…”
mentioning
confidence: 97%